(untitled) (International Nexus Multidisciplinary Research Journal, 2025)
The main purpose of the study was to explore artificial intelligence and future in school management. (the transformative potential of AI in modernizing school administrative and pedagogical systems, focusing on how artificial intelligent technologies can enhance school administration).the study adopted a descriptive survey research design. The population of the study consist of 329 principals and 8628 teachers in Enugu state, A sample of 896 (33 principals and 863 teachers) using Taro Yamane method of sampling was used .The instrument used for data collection was questionnaire developed by the researcher. titled Artificial Intelligence And Future School Management In Secondary Schools In Enugu state (AIFSM). A 17 item questionnaire grouped into 3 sections according to the research question that guided the study. The items were structured in four rating. The reliability of the instrument was determined using test-retest reliability techniques. Out of 896 copies distributed 850 were properly filled and retrieved representing 92% retune rate. Mean and standard deviation was used for data analysis while t-test statistic was used to test the null hypothesis at 0.05 level of significance. Based on the data analysis ,the study conclude that AI for administrative efficiency in secondary school in Enugu state depends on the perception and readiness of educators, availabilities of AI tools ,its implementation and establishing a clear policy framework to guide it use . Among the Recommendations made based on the findings of the study, AI solutions should be implemented with a strong emphasis on Promoting Equity and Accessibility, eliminating educational inequalities. Schools in low-income or rural areas must have access to AI tools and the infrastructure necessary to support them.